Development of a Durable PEMFC Startup Process by Applying a Dummy Load - Kim, Jae Hong; Cho, Eun Ae; Jang, Jong Hyun; Kim, Hyoung Juhn; Lim, Tae-Hoon; Oh, In-Hwan; Ko, Jae Jun; Oh, Seung Chan (ELECTROCHEMICAL SOC INC, 2009)
Various polymer electrolyte membrane fuel cell (PEMFC) startup procedures were tested to explore possible techniques for reducing performance decay and improving durability during repeated startup-shutdown cycles. The effects of applying a dummy load, which prevents cell reversal by consuming the air at the cathode, on the degradation of a membrane electrode assembly were investigated via single-cell experiments. Electrochemical techniques, including measurement of polarization curves, electrochemical impedance spectroscopy, cyclic voltammetry, and linear sweep voltammetry, were employed to investigate the degradation of the PEMFCs. The results showed that application of a dummy load during the startup procedure significantly reduced the performance decay, the decrease in the electrochemically active surface area, and the increase in charge-transfer resistance (R-ct), which resulted in a dramatic improvement in durability. Our results suggest that starting up PEMFCs while applying a dummy load is an effective method for mitigating performance degradation caused by cell reversal under a repetition of unprotected startup cycles.
Keywords: FUEL-CELL; CARBON CORROSION; DEGRADATION; DURABILITY; STARVATION; CATALYST; DAMAGE